PENERAPAN MODEL PEMBELAJARAN READING GUIDE DALAM MENINGAKTKAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM MATERI MUJAHADAH AN-NAFS DI SMA NEGERI 5 MALANG - Tarisa Wanda Lutfiah; Muhammad Hanief; Muhammad Fahmi Hidayatullah (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study discusses the application of the reading guide learning model used by PAI teachers in improving student achievement at SMAN 5 Malang. Student achievement is indeed very important because learning achievement is a skill or mastery of student knowledge developed by subjects in the form of values or numbers. If students have good achievements, it can improve student achievement as well. Therefore, it is necessary to apply the right method used by teachers in improving student achievement. This research is used to provide innovation to teachers about the application of appropriate learning models and can be used in improving student achievement. The research approach used is a descriptive qualitative approach, which is a method to find data or information with the aim of being clearly explained, starting from the design of objectives, approaches, and data collection processes as material for making reports. From the discussion above, it can be concluded that the application of the reading guide model in improving student achievement in mujahadah an-nafs material is through understanding, example and also habituation.